Ultrafast Dynamics of the Transoid‐cis Isomer Formed in Photochromic Reaction from 3H‐Naphthopyran. Issue 13 (8th June 2020) - Brazevic, Sabina; Baranowski, Mikołaj; Sikorski, Marek; Rode, Michał F.; Burdziński, Gotard
Abstract: Recent efforts in designing new 3 H ‐naphthopyran derivatives have been focused on efficient coloration process with a short fading time of the colored transoid‐ cis TC isomer. It is desirable to avoid photoisomerization of TC leading to transoid‐ trans TT isomers in the photoreaction. Long lifetime of TT can hamper fast applications such as dynamic holographic materials and molecular actuators, the residual color is one of the serious issues for photochromic lenses. Herein we characterize the photophysical and photochemical channels of TC excited state deactivation competing with the unwanted TC →TT isomerization process. Transient absorption spectroscopy reveals a very short lifetime of the singlet excited TC (≈0.8 ps) and its deactivation channels as S1 →S0 internal conversion (major), intersystem crossing S1 →T1, pyran ring formation, photoenolization and TC →TT isomerization. Computations support the S1 →S0 and T1 →S0 channels as responsible for photostabilization of the TC form. Abstract : Competing with isomerization : Photoexcitation is followed by efficient S1 →S0 internal conversion (major) proceeding through S1 /S0 conical intersection in competition with transoid‐ cis →transoid‐ trans isomerization. Increase in the internal conversion rate may reduce yield of the unwanted transoid‐ trans form in the photochromic reaction of 3 H ‐naphthopyrans.